Recent Trends in Power Transformer Fault Diagnosis and Condition Assessment - Zakir Husain; Hasmat Malik; Mohd. Arif Khan (Bulletin of Electrical Engineering and Informatics, 2013)
Power transformers are interface between different voltage levels of essential importance. Because of the long manufacturing processes, transformers are one of the most critical and expensive equipment and so this is one of the reasons why condition monitoring becomes more popular. Monitoring systems as basis for diagnostics open the possibility for expanding the operating time, reducing the risk of expensive failures and allows several maintenance strategies. With different monitoring techniques, detailed informations about the transformer condition can be received and helps to minimize the probability of an unexpected outage. In this paper a methodology has been developed to use information derived from condition monitoring and diagnostics for rehabilitation purposes of transformers. The interpretation and understanding of the test data are obtained from the International Standards.